Organic signatures of fireplaces: Experimental references for archaeological interpretations. (September 2016) - Lejay, Mathieu; Alexis, Marie; Quénéa, Katell; Sellami, Farid; Bon, François
Highlights: Bone fires led to an increase in soil OC, but no variation was noticed for wood fire. Soil lipids and bulk OM reflected type of fuel used for experimental fires. Soil lipids and bulk OM revealed byproducts of thermal alteration. Organic signatures from experimental fireplaces provide a reference for archaeological applications. Abstract: The use of fire is a well-established human practice, at least from the Late Pleistocene. The variability in fuel type highlights complex practices regarding fire technology throughout this period. This contribution provides the organic signatures from fireplaces and is based on a set of experimental studies using different types of fuel, notably bone and/or wood. Soil layers affected by fire operation were compared with soils unaffected by heating and soils impregnated with unburned bone fat. The carbon content and lipid and bulk organic matter (OM) composition were determined through organic carbon measurement, gas chromatography–mass spectrometry (GC–MS), as well as TMAH (tetramethylammonium hydroxide)-assisted pyrolysis (py) coupled to GC–MS. With the exception of the wood-fueled fireplace, an increase in organic carbon content was caused by fireplace operation. The products of triacylglycerol degradation (diacids, oxo-acids and glycerol derivatives) reflected the contribution from animal fat affected by the oxidation process with or without thermal alteration. The branched unsaturated C9:0 and C10:0 acids were detected only in py(TMAH)–GC–MS of soil impregnated with bone fat that was not thermally altered. The branched diacids, ketones and lactones detected in lipid extracts, and short chain acids and n- alkane/ n- alkene doublets detected with py(TMAH–GC–MS), were produced by thermal alteration of animal fat. Finally, in the fireplace fueled with wood only, phenolic compounds, benzoic acids and benzene derivatives were detected and reflected the contribution of charred and uncharred plant OM. The results extend the organic signatures obtained from an experimental reference dataset, specifically for the identification of fuel type used in fireplaces.